2019
DOI: 10.1155/2019/3610965
|View full text |Cite
|
Sign up to set email alerts
|

Additional Evidence forDDB2T338M as a Genetic Risk Factor for Ocular Squamous Cell Carcinoma in Horses

Abstract: Squamous cell carcinoma (SCC) is the most common periocular cancer in horses and the second most common tumor of the horse overall. A missense mutation in damage-specific DNA-binding protein 2 (DDB2, c.1012 C>T, p.Thr338Met) was previously found to be strongly associated with ocular SCC in Haflinger and Belgian horses, explaining 76% of cases across both breeds. To determine if this same variant in DDB2 contributes to risk for ocular SCC in the Arabian, Appaloosa, and Percheron breeds and to determine if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…While risk for ocular SCC has been highly correlated with the DDB2 genotype, not all cases of ocular SCC were explained by homozygosity for this variant. Genetic heterogeneity is likely involved [18]. In our study, the mean age of diagnosis from two retrospective data sets was found to be 14.11 ± 5.39 years, consistent with what is reported in the literature [10].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…While risk for ocular SCC has been highly correlated with the DDB2 genotype, not all cases of ocular SCC were explained by homozygosity for this variant. Genetic heterogeneity is likely involved [18]. In our study, the mean age of diagnosis from two retrospective data sets was found to be 14.11 ± 5.39 years, consistent with what is reported in the literature [10].…”
Section: Discussionsupporting
confidence: 91%
“…The aim of this work was to determine if the known risk variant (DDB2 c.1013C>T) could have led to the development of SCC in the affected Holsteiner cross and the two affected Connemara Ponies and these data support this to be the case. Other potential risk factors for SCC development have been studied previously, including age, sex, coat color, and equine papilloma virus type 2 infection [18]. While risk for ocular SCC has been highly correlated with the DDB2 genotype, not all cases of ocular SCC were explained by homozygosity for this variant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations